Knowledge, attitudes, and practices towards COVID-19 among Nepalese Residents: A quick online cross-sectional survey - Hussain, Asraf; Garima, Tripathi; Singh, Bishnu Mohan; Ram, Ramji; Tripti, Raman Pal (Asian Journal of Medical Sciences, 2020)
Background: Corona virus disease 2019 (COVID-19) is a highly infectious disease. It is caused by a novel virus belonging to a family known as corona virus. This virus was first identified in the month December 2019 in Wuhan, China Hubei province. Since its first identification it has spread globally. It was declared a public health emergency of international concern on January 30, 2020 by WHO. Despite all efforts the virus continues to spread and WHO declared it a pandemic on March 11, 2020. In Nepal the first case was tested positive on 23rd January and ever since numbers are increasing as days passed by. Residents of the country are the most important stakeholders to control the spread of such viruses. Nepal is a land locked country situated between India and China and is one of the vulnerable areas among SAARC nations. In spite of being such a vulnerable nation there was a lack of previous studies detecting the degree of awareness among Nepalese residents towards COVID 19. Aims and Objectives: This study aims to assess the current level of awareness towards COVID 19 among Nepalese residents and to analyze their attitudes and practices towards COVID 19 which is very important for people’s active participation to control this pandemic. In this study we investigated Nepalese residents KAP towards COVID-19. Material and Methods: This is cross sectional online study. A self-developed online questionnaire was completed by the participants. There were a total 29 questions among which 15 questions assessed knowledge, 6 questions assessed attitude and remaining 8 questions assessed practice. Results: Among the respondents (n=760), 65.7 % were male, 50.3 % were healthcare workers, overall range of correct answers for knowledge questionnaire was 60.0-98.7%, that for attitude was 77.9-96.4% and for practice was 78.2-95.0 %. Participants with a medical degree had statistically significant better practice against COVID 19 compared with the general population. Conclusion: Findings of this study show that knowledge among people of Nepal about COVID 19 is satisfactory. Yet a significant number of participants are lacking confidence when compared to other countries. Better practice against COVID requires a sense of responsibility, though the respondents with medical background had better sense of act against COVID prevention practice.